Identification of Differently Expressed Genes Associated With Prognosis and Growth in Colon Adenocarcinoma Based on Integrated Bioinformatics Analysis - Hu, Ming; Fu, Xiandong; Si, Zhaoming; Li, Chunming; Sun, Jihu; Du, Xinna; Zhang, Hu (Frontiers in Genetics, 2019)
Latest statistics showed that the morbidity and mortality of colon adenocarcinoma (COAD) ranked 4th and 5th respectively around the world. COAD was a heterogeneous disease, and the high rates of recurrence, metastasis and drug resistance still posed great challenges for the treatment, which needs to further develop therapeutic and prognostic targets. In this study, we got top 3075 differently expressed genes (DEGs) and 1613 potential prognostic genes by GEPIA 2, and identified 1166 fitness genes in COAD based on Genome-scale CRISPR-Cas9 knockout (GeCKO) screening data. Excluding the genes already reported in the literatures, a total of 9 DEGs overlapping with prognostic and fitness genes were further analyzed. High expression of CCT6A, RHOQ and RRP12 promoted COAD cell growth and were relative to lower survival rate of COAD patients, while high expression of UTP18, DDOST, YRDC, ACTG1, RFT1 and NLE1 also promoted COAD cell growth but were relative to higher survival rate. In addition, CCT6A, UTP18, YRDC, RRP12, RFT1, NLE1 as well as DDOST were essential genes across pan-cancer including COAD cells, and ACTG1 and RHOQ were less essential genes in cancer cells. In a word, we discovered 9 novel potential genes that could serve as anti-cancer targets and prognostic markers in COAD and its subtypes.